AB1418-PC Impact of the physiotherapy unit in an urban primary care health centre. (23rd January 2014) - Julian, R.; Ramirez, R.; Rueda, M.J.; Latorre, A.; Castell, V.; Melgar, A.; Martin, L.; Duran, E.
Abstract : Background: Primary Care Physiotherapy Units attend patients derived by primary care physicians with the next care circumstances: degenerative osteomuscular disease, specially spinal osteoarthritis; but also pain located in shoulder, knee, hand and hip. Pathology of ligaments (sprains), tendinitis and bursitis are also treated. The physiotherapists of the primary care unit don't treat pathology produced by trauma (fractures), or neuronal disease. Patients receive 10 sessions of physical therapy lasting about 50 minutes and involving the application of different techniques assessed by the physiotherapist depending on location, pathology and severity of injury: Treatment procedures available include:cryotherapy, thermotherapy, electrotherapy (like Transcutaneous Electrical Nervous Stimulation or TENS), exercise (joint range, strengthening, re-education), manual therapy, and postural hygiene. Objectives: To describe the population who received treatment in a Primary Care Physiotherapy Unit, the type of pathology treated, and to quantify the improvement in pain reduction after treatment. Methods: Design: An observational retrospective study was used. Subjects: All the patients attended during a year. Setting: Primary Care Physiotherapy Unit. from an urban Primary Care Centre. Variables assessed: age, sex, disease for which is derived for treatment, pain reduction and poortreatmentcompletion. Results: Out of 867 people were attended in the Physiotherapy Unit. 71, 9% of them were women. The standard age rate was 61, 13 (± 16, 37), and the age status was from 16 to 90 years old. The attended pathologies in order of frequency were: neck pain (29, 5%), low back pain (25, 3%), shoulder pain (21, 2%), knee pain (9, 1%), dorsal back pain (4, 8%), hand pain (3, %); sprains (2, 9%), tendinitis (2, 2%) and hip pain (1, 5%). After 10 sessions of physiotherapy, effectiveness of treatment is seen by significant reduction of pain in 53, 1%, partial reduction in 39, 2%, and no noticeable improvement in 1, 2%. The dropout rate was 6, 5%. Conclusions: The profile of patients seen at the physiotherapy unit of primary care is that of a middle-aged woman (61 years) presenting degenerative spinal disease. The physical therapy is highly effective in the reduction of the pain (92% of the patients recounts some improvement and only 6, 5% did not finish the treatment). Primary Care Physiotherapy Units greatly reduce referral to the second level of care and improve user accessibility and quality of life. References: Gόmez-Conesa, A; Abril Belchí, E. Physiotherapy Activity of Spinal Diseases in Primary Healthcare. Fisioterapia. 2006; 28(4):217-25 Abril E, Gόmez A, Gutierrez –Santos M. Assessment and improvement of the care protocol for patients with lumbar pathology in a primary health care physiotherapy unit. Rev Calidad Asistencial 2008; 23 (3): 109-13 Disclosure of Interest: None Declared